PENGARUH INDEPENDENSI, AUDIT FEE, DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT - Kusumawardani, Diah; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the influence of independency, audit fee, and objectivity on audit quality. Therespondents are all auditorâs staffs with the position from junior up to manager who work at Public AccountingOffice Surabaya. The sample are 8 Public Accounting Offices which are represented by 46 auditorâs staffs whohave been selected by using simple random sampling method. The data of this research has been obtained byissuing questionnaires directly shared to the respondents in the middle of November 2015. The analysistechnique has been done by using multiple linear regressions analysis. The result of this research has provedthat: (a) independency has positive influence to the audit quality, it means that when an auditor is independentso that the quality of an auditor is well; (b) audit fee has positive influence to the audit quality, it means thataudit fee can support the complexity of the service which has been provided by the auditor so that it will giveboost the good quality of the audit of the auditor; (c) objectivity has positive influence to the audit quality, itmeans that auditor cannot be stated have a good quality when the auditor does not act objectively based on theauthentic evidences from the existing fact that have been obtained.Keywords: Independency, Audit Fee, Objectivity, Audit Quality.